The Role of Information Technology in Enhancing Transparency and Relevance of Financial Reporting Values: Systematic Literature Review (2020–2025) - Shara Ketty Moretta Situmorang; Sambas Ade Kesuma; Fahmi Natigor Nasution; Keulana Erwin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The development of information technology has brought about significant transformations in global financial reporting practices. The digitalization within the domain of financial reporting, notably marked by the utilization of the extensible Business Reporting Language (XBRL) standard, Digital Financial Reporting (DFR), and big data-based disclosure systems, has become a major focus of research in the last decade. This study aims to identify trends, gaps, and future research directions regarding the role of information technology in improving the transparency and value relevance of financial reports through a Systematic Literature Review (SLR) approach to 10 international scientific articles indexed by Scopus published in the period 2020–2025. The research method used the PRISMA approach, which includes identification, screening, feasibility, and inclusion. The analysis was conducted by grouping the research results based on key themes such as corporate governance, XBRL adoption, financial information transparency, and the impact of technological advancements on the value relevance of financial information. The study's findings indicate that the use of information technology serves as a key driver in enhancing the quality, accessibility, and reliability of financial reporting. However, the effectiveness of its implementation varies across countries, depending on the readiness of infrastructure, regulations, and corporate governance. Furthermore, research gaps were identified regarding the integration of XBRL, climate change disclosure, and the concept of double materiality in sustainability reporting.This research provides an academic contribution in mapping the development of the concept of digital financial reporting and the direction of future research, particularly regarding the integration of big data-based information systems and artificial intelligence (AI) in corporate reporting